Fluorine-doped CeO2 abrasive particle as well as preparation method and application thereof
The preparation of fluorine-doped CeO2 abrasive particles by two-step method has solved the problems of uneven particle size and poor suspension stability of the existing CeO2 abrasive particles, and achieved efficient chemical mechanical polishing and surface processing effects.
Patent Information
- Application Number
- CN202411283664.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-13
- Publication Date
- 2024-12-17
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
During the polishing process, the existing CeO2 abrasive particles have problems such as uneven particle size, easy agglomeration, and poor suspension stability, resulting in high surface roughness and low material removal rate.
The fluorine-doped CeO2 abrasive particles were prepared by two-step method. By adjusting the roasting system, the controllable particle size distribution of 75-100nm is achieved, and spherical fluorine-doped CeO2 abrasive particles were formed. Dilute nitric acid and ammonia water were added to the polishing liquid to adjust the pH value, and the pH value was increased. Suspension stability.
Fluorine-doped CeO2 abrasive particles with uniform particle size distribution and good dispersion are achieved, which improves the chemical mechanical polishing and suspension stability of the polishing liquid, and significantly improves the material removal rate and surface quality.
Smart Images

Figure CN119144286A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of functional materials, relates to chemical mechanical polishing materials, and specifically relates to fluorine-doped CeO2 abrasive particles and a preparation method and application thereof. Background Art
[0002] Chemical Mechanical Polishing (CMP) is currently the only technology that can achieve global surface flattening. Compared with traditional chemical polishing and mechanical polishing processes, chemical mechanical polishing effectively avoids the surface damage (such as scratches, pits, etc.) caused by pure mechanical polishing and the shortcomings of low material removal rate, low surface flatness and poor consistency caused by pure chemical polishing technology. Chemical mechanical polishing mainly uses the synergistic effect of chemical reaction and mechanical removal to achieve surface smoothness.
[0003] The main components of polishing liquid are abrasive, dispersant, oxidant, pH regulator, surfactant, etc. Among the various components of polishing liquid, abrasive is undoubtedly the most important core component. At present, the most common abrasives are Al2O3, SiO2 and CeO2. Al2O3 abrasives have high hardness and fast polishing rate. However, Al2O3 polishing liquid has the disadvantages of poor polishing selectivity, poor suspension stability, and easy agglomeration of abrasives, which can easily cause serious scratches on the polishing surface. SiO2 abrasives have good stability and dispersibility, and their hardness is close to that of elemental silicon. They cause fewer scratches and marks to the substrate material, but their material removal rate is relatively low. CeO2 abrasives are widely used in the CMP process of SiO2 materials due to their suitable mechanical properties and chemical activity, which bring high efficiency and high-quality polishing.
[0004] During the polishing process, there is not only Ce on the surface of CeO2 abrasive particles 4+ , there is also a certain amount of Ce 3+ , by increasing Ce 3+ The content of CeO2 can effectively improve the polishing efficiency of CeO2 abrasives. In order to obtain better CMP performance, CeO2 abrasives are doped and modified. Doping modification is an effective means to regulate the surface chemical state of CeO2 abrasives. 3+ Concentration. Secondly, the suspension stability of the polishing liquid is also one of the important factors affecting CMP performance. Because CeO2 abrasive particles have quantum size effect and surface effect, they will easily agglomerate, which will lead to large surface roughness of the polished material. Summary of the invention
[0005] In view of the shortcomings of the prior art, the present invention aims to provide a spherical fluorine-doped CeO2 abrasive with uniform particle size distribution and good dispersibility, and a preparation method and application thereof. The synthesis method is simple and the size is controllable. The polishing liquid has excellent chemical mechanical polishing and good suspension stability.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions:
[0007] A method for preparing fluorine-doped CeO2 abrasive particles comprises the following steps:
[0008] Step 1: weigh the raw materials according to the molar ratio of cerium source to soluble carbonate precipitant of 1:(0.5-5), and dissolve them in water respectively to prepare cerium source solution and precipitant solution with molar concentration of 0.1-0.5 mol / L respectively;
[0009] Step 2: Place the cerium source solution obtained in step 1 in a water bath at 25°C to 80°C, and add the precipitant solution dropwise while stirring to form a reaction solution;
[0010] Step 3, stirring the reaction solution in step 2 until it is evenly mixed, and then performing an aging reaction in a water bath at 25° C. to 90° C. for 1 h to 48 h; after the aging reaction, centrifuging and washing the precipitate, and finally drying the precipitate in an oven to obtain a cerium-based precursor;
[0011] Step 4: Take the cerium-based precursor, molten salt and fluorinating agent in step 3 in a molar ratio of 1: (3-12): (0.01-0.09), grind the three raw materials separately, disperse them in anhydrous ethanol, stir them magnetically until they are evenly mixed, and then dry them to obtain a mixed salt;
[0012] Step 5: Place the mixed salt obtained in step 4 into a muffle furnace at 700°C to 900°C for calcination for 2h to 6h, and finally allow it to cool naturally to room temperature. Wash and dry the reaction product to obtain fluorine-doped CeO2 abrasive.
[0013] The present invention also has the following technical features:
[0014] Preferably, the cerium source includes any one of cerium nitrate hexahydrate, cerium chloride hexahydrate, and cerium carbonate.
[0015] Preferably, the soluble carbonate precipitant includes any one of anhydrous sodium carbonate, ammonium carbonate and ammonium bicarbonate.
[0016] Preferably, the stirring time in step three is 0.5h to 2h.
[0017] Preferably, the molten salt described in step 4 includes a mixture of any two or more of potassium chloride, potassium nitrate, sodium chloride, sodium nitrate and lithium chloride.
[0018] Preferably, the fluorinating agent in step 4 includes any one of potassium fluoride, sodium fluoride and ammonium fluoride.
[0019] Preferably, the magnetic stirring time in step 4 is 20 min to 40 min.
[0020] The present invention also protects a fluorine-doped CeO2 abrasive prepared by the method as described above and its application in chemical mechanical polishing, wherein the stoichiometric formula of the fluorine-doped CeO2 abrasive is CeO 2-x F x , (0.01≤x≤0.09); size is 75~100nm.
[0021] The following steps are used to prepare the fluorine-doped CeO2 abrasive polishing liquid:
[0022] Step 1: Disperse the fluorine-doped CeO2 abrasive in deionized water and perform ball milling for 6 to 10 hours;
[0023] Step 2: Use dilute nitric acid and ammonia water to adjust the pH value of the dispersion prepared in step 1 to 6, and adjust the solid content to 0.5wt% to obtain a fluorine-doped CeO2 abrasive polishing liquid with high activity and high suspension stability for chemical mechanical polishing.
[0024] Compared with the prior art, the present invention has the following technical effects:
[0025] The present invention adopts a two-step method to synthesize spherical fluorine-doped CeO2 abrasive particles with microscopic morphology. By adjusting the roasting system, controllable preparation of 75-100nm fluorine-doped CeO2 abrasive particles can be achieved. The synthesis method is simple, the size is controllable, the particle size distribution is uniform, the dispersion is good, and the spherical fluorine-doped CeO2 abrasive particles are produced. The fluorine-doped CeO2 abrasive polishing liquid has excellent chemical mechanical polishing properties and good suspension stability, slow sedimentation rate, large absorbance and large absolute value of Zeta potential.
[0026] The polishing liquid prepared by the spherical fluorine-doped CeO2 abrasive particles synthesized by the present invention is used to carry out surface processing on quartz glass, and the material removal rate reaches 819.89 nm / min, and a high material removal rate is obtained. This is attributed to the high chemical activity of the fluorine-doped CeO2 abrasive particles synthesized by the two-step method of the present invention, which helps to improve the material removal rate. It is found through sedimentation tests that the suspension and dispersion stability of the fluorine-doped CeO2 abrasive particles is improved; it is found through sedimentation tests that the suspension and dispersion stability of the fluorine-doped CeO2 abrasive particles is improved, which is conducive to the improvement of surface quality. Under the condition of the best dispersion, the best surface roughness is 0.2008 nm. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 XRD patterns of the fluorine-doped CeO2 abrasives of Examples 1-5 and the CeO2 abrasives of Comparative Example 1;
[0028] Figure 2 The SEM images of the fluorine-doped CeO2 abrasives of Examples 1-5 and the CeO2 abrasives of Comparative Example 1;
[0029] Figure 3 The particle size distribution diagram of the fluorine-doped CeO2 abrasive particles of Examples 1-5 and the CeO2 abrasive particles of Comparative Example 1;
[0030] Figure 4 A comparison chart of the chemical mechanical polishing material removal rate and surface roughness of the fluorine-doped CeO2 of Examples 1-5 and the CeO2 polishing solution of Comparative Example 1 on the SiO2 substrate;
[0031] Figure 5 An atomic force microscope image of the surface of the SiO2 glass of Example 3;
[0032] Figure 6 Schematic diagram of the sedimentation of fluorine-doped CeO2 polishing liquid in Examples 1-5 and Comparative Example 1 CeO2 polishing liquid. DETAILED DESCRIPTION
[0033] The present invention is further described in detail below in conjunction with specific embodiments.
[0034] Example 1
[0035] Step 1: According to the molar ratio of cerium source to precipitant of 1:0.5, 2.1711 g (0.005 mol) of cerium nitrate hexahydrate and 0.265 g (0.0025 mol) of anhydrous sodium carbonate were weighed and dissolved in deionized water to prepare a cerium source solution and a precipitant solution with a concentration of 0.5 mol / L;
[0036] Step 2: Place the cerium source solution obtained in step 1 in a 60° C. water bath, add the precipitant solution dropwise while stirring to form a reaction solution;
[0037] Step 3, the reaction solution in step 2 is stirred for 1 hour, and then aged in a water bath at 60° C. for 4 hours. After the reaction is completed, the precipitate is centrifuged, washed, and finally dried in an oven to obtain a cerium-based precursor;
[0038] Step 4: Weigh 1.0796 g (0.004975 mol) of cerium-based precursor, 1.8544 g (0.0249 mol) of potassium chloride, 1.4552 g (0.0249 mol) of sodium chloride, and then weigh 0.01452 g (0.00025 mol) of potassium fluoride, grind them separately, and then evenly disperse them in anhydrous ethanol, stir them magnetically for 30 minutes, and then dry them in a constant temperature drying oven at 80° C. for 5 hours to obtain a mixed salt;
[0039] Step 5: Put the mixed salt obtained in step 4 into a crucible, place it in a muffle furnace, heat it from room temperature to 800°C at 5°C / min, keep it warm for 4 hours, and then calcine it. Then, cool it to 400°C at 2°C / min. Finally, cool it naturally to room temperature, wash it with deionized water for 5 times, and dry it in a constant temperature drying oven at 80°C for 5 hours to obtain fluorine-doped CeO2 abrasive particles, represented by CeO 1.99 F 0.01 Abrasive particles.
[0040] The obtained CeO 1.99 F 0.01 The abrasive particles were dispersed in deionized water and ball-milled for 10 hours. The pH value of the dispersion prepared in step 1 was adjusted to 6 with dilute nitric acid and ammonia water, and the solid content was adjusted to 0.5wt% to obtain a polishing liquid with a solid content of 0.5wt%, which was applied to a SiO2 substrate for chemical mechanical polishing. The polishing machine model was UNIPOL-1200S automatic pressure grinding and polishing machine, the lower polishing disc speed was 80r / min, the polishing head speed was 80r / min, the downward pressure was 3.5kg, the polishing time was 180s, and the material removal rate was calculated by weighing the average value of the change in glass mass before and after polishing. An atomic force microscope (AFM) was used to observe the change in surface roughness of the polished workpiece before and after polishing.
[0041] After the prepared polishing liquid is dispersed, a portion is measured and placed in a 10 ml sub-bottle for a 5-day sedimentation test to test the suspension stability of the polishing liquid. The supernatant after sedimentation for several days is then used for other tests such as absorbance and Zeta potential to characterize the suspension stability of the polishing liquid.
[0042] Example 2
[0043] Step 1: According to the molar ratio of cerium source to precipitant of 1:1, 2.1711 g (0.005 mol) of cerium nitrate hexahydrate and 0.530 g (0.005 mol) of anhydrous sodium carbonate were weighed and dissolved in deionized water to prepare a cerium source solution and a precipitant solution with a concentration of 0.3 mol / L respectively;
[0044] Step 2: Stir the cerium source solution obtained in step 1 in a water bath at 50° C., and add the precipitant solution dropwise to form a reaction solution;
[0045] Step 3, the reaction solution in step 2 is stirred for 0.8h, and then aged in a water bath at 25°C; after the aging reaction is completed for 1h, the precipitate is centrifuged, washed, and finally dried in an oven to obtain a cerium-based precursor;
[0046] Step 4: Weigh 1.0687 g (0.004925 mol) of cerium-based precursor, 1.8358 g (0.0246 mol) of potassium chloride, 1.4406 g (0.0246 mol) of sodium chloride, and then weigh 0.0435 g (0.00075 mol) of potassium fluoride, grind them separately, and then evenly disperse them in anhydrous ethanol, stir them magnetically for 20 minutes, and then dry them in a constant temperature drying oven at 60° C. for 12 hours to obtain a mixed salt;
[0047] Step 5: Put the mixed salt obtained in step 4 into a crucible, place it in a muffle furnace, heat it from room temperature to 750°C at 5°C / min, keep it warm for 3 hours, calcine it, then cool it to 400°C at 2°C / min, and finally cool it naturally to room temperature. After washing it with deionized water for 5 times, dry it in a constant temperature drying oven at 80°C for 5 hours to obtain CeO 1.97 F 0.03 Abrasive particles.
[0048] The obtained CeO 1.97 F 0.03 The abrasive particles were dispersed in deionized water and ball-milled for 6 hours. The pH value of the dispersion prepared in step 1 was adjusted to 6 with dilute nitric acid and ammonia water, and the solid content was adjusted to 0.5wt% to obtain a polishing liquid with a solid content of 0.5wt%, which was applied to a SiO2 substrate for chemical mechanical polishing. The polishing machine model was UNIPOL-1200S automatic pressure grinding and polishing machine, the lower polishing disc speed was 80r / min, the polishing head speed was 80r / min, the downward pressure was 3.5kg, the polishing time was 180s, and the material removal rate was calculated by weighing the average change in glass mass before and after polishing. An atomic force microscope (AFM) was used to observe the change in surface roughness of the polished workpiece before and after polishing.
[0049] After the prepared polishing liquid is dispersed, a portion is measured and placed in a 10 ml sub-bottle for a 5-day sedimentation test to test the suspension stability of the polishing liquid. The supernatant after sedimentation for several days is then used for other tests such as absorbance and Zeta potential to characterize the suspension stability of the polishing liquid.
[0050] Example 3
[0051] Step 1: According to the molar ratio of cerium source to precipitant of 1:2, 1.7728 g (0.005 mol) of cerium chloride hexahydrate and 0.9608 g (0.01 mol) of ammonium carbonate were weighed, and dissolved in deionized water to prepare a cerium source solution and a precipitant solution with a concentration of 0.1 mol / L;
[0052] Step 2: Stir the cerium source solution obtained in step 1 in a water bath at 25° C., and add the precipitant solution dropwise to form a reaction solution;
[0053] Step 3, the reaction solution in step 2 is stirred for 1.5 hours, and then aged in a water bath at 90°C; after the aging reaction is completed for 36 hours, the precipitate is centrifuged, washed, and finally dried in an oven; thus, a cerium-based precursor is obtained;
[0054] Step 4: Weigh 1.0579 g (0.004875 mol) of cerium-based precursor, 2.4668 g (0.0244 mol) of potassium nitrate, 2.0737 g (0.0244 mol) of sodium nitrate, and then weigh 0.00726 g (0.000125 mol) of potassium fluoride, grind them separately, and then evenly disperse them in anhydrous ethanol, stir them magnetically for 40 minutes, and then dry them in a constant temperature drying oven at 90° C. for 6 hours to obtain a mixed salt;
[0055] Step 5: Put the mixed salt obtained in step 4 into a crucible, place it in a muffle furnace, heat it from room temperature to 700°C at 5°C / min, keep it warm for 6 hours, calcine it, then cool it to 400°C at 2°C / min, and finally cool it naturally to room temperature. After washing it with deionized water for 5 times, dry it in a constant temperature drying oven at 80°C for 5 hours to obtain CeO 1.95 F 0.05 Abrasive particles.
[0056] The obtained CeO 1.95 F 0.05 The abrasive particles were dispersed in deionized water and ball-milled for 8 hours. The pH value of the dispersion prepared in step 1 was adjusted to 6 with dilute nitric acid and ammonia water, and the solid content was adjusted to 0.5wt% to obtain a polishing liquid with a solid content of 0.5wt%, which was applied to a SiO2 substrate for chemical mechanical polishing. The polishing machine model was UNIPOL-1200S automatic pressure grinding and polishing machine, the lower polishing disc speed was 80r / min, the polishing head speed was 80r / min, the downward pressure was 3.5kg, the polishing time was 180s, and the material removal rate was calculated by weighing the average change in glass mass before and after polishing. An atomic force microscope (AFM) was used to observe the change in surface roughness of the polished workpiece before and after polishing.
[0057] After the prepared polishing liquid is dispersed, a portion is measured and placed in a 10 ml sub-bottle for a 5-day sedimentation test to test the suspension stability of the polishing liquid. The supernatant after sedimentation for several days is then used for other tests such as absorbance and Zeta potential to characterize the suspension stability of the polishing liquid.
[0058] Example 4
[0059] Step 1: According to the molar ratio of cerium source to precipitant of 1:5, 2.3013 g (0.005 mol) of cerium carbonate and 1.9763 g (0.025 mol) of ammonium bicarbonate were weighed, and dissolved in deionized water to prepare a cerium source solution and a precipitant solution with a concentration of 0.2 mol / L;
[0060] Step 2: Stir the cerium source solution obtained in step 1 in a water bath at 70° C., and add the precipitant solution dropwise to form a reaction solution;
[0061] Step 3, the reaction solution in step 2 is stirred for 0.5h, and then aged in a water bath at 40°C; after the aging reaction is completed for 24h, the precipitate is centrifuged, washed, and finally dried in an oven; thus, a cerium-based precursor is obtained;
[0062] Step 4: Weigh 1.0470 g (0.004825 mol) of cerium-based precursor, 2.1582 g (0.0289 mol) of potassium chloride, 1.2251 g (0.0289 mol) of lithium chloride, and then weigh 0.0435 g (0.00075 mol) of potassium fluoride, grind them separately, and then evenly disperse them in anhydrous ethanol, stir them magnetically for 30 minutes, and then dry them in a constant temperature drying oven at 80° C. for 5 hours to obtain a mixed salt;
[0063] Step 5: Put the mixed salt obtained in step 4 into a crucible, place it in a muffle furnace, heat it from room temperature to 900°C at 5°C / min, keep it warm for 2h, calcine it, then cool it to 400°C at 2°C / min, and finally cool it naturally to room temperature, wash it with deionized water for 5 times, and dry it in a constant temperature drying oven at 80°C for 5h to obtain CeO 1.93 F 0.07 Abrasive particles.
[0064] The obtained CeO 1.93 F 0.07The abrasive particles were dispersed in deionized water and ball-milled for 10 hours. The pH value of the dispersion prepared in step 1 was adjusted to 6 with dilute nitric acid and ammonia water, and the solid content was adjusted to 0.5wt% to obtain a polishing liquid with a solid content of 0.5wt%, which was applied to a SiO2 substrate for chemical mechanical polishing. The polishing machine model was UNIPOL-1200S automatic pressure grinding and polishing machine, the lower polishing disc speed was 80r / min, the polishing head speed was 80r / min, the downward pressure was 3.5kg, the polishing time was 180s, the material removal rate was calculated by weighing the average change in glass mass before and after polishing, and an atomic force microscope (AFM) was used to observe the change in surface roughness of the polished workpiece before and after polishing.
[0065] After the prepared polishing liquid is dispersed, a portion is measured and placed in a 10 ml sub-bottle for a 5-day sedimentation test to test the suspension stability of the polishing liquid. The supernatant after sedimentation for several days is then used for other tests such as absorbance and Zeta potential to characterize the suspension stability of the polishing liquid.
[0066] Example 5
[0067] Step 1: According to the molar ratio of cerium source to precipitant of 1:0.5, 2.1711 g (0.005 mol) of cerium nitrate hexahydrate and 0.265 g (0.0025 mol) of anhydrous sodium carbonate were weighed and dissolved in deionized water to prepare a cerium source solution and a precipitant solution with a concentration of 0.4 mol / L;
[0068] Step 2: Stir the cerium source solution obtained in step 1 in a water bath at 80° C., and add the precipitant solution dropwise to form a reaction solution;
[0069] Step 3, the reaction solution in step 2 is stirred for 2 hours, and then aged in a water bath at 70°C; after the aging reaction is completed for 48 hours, the precipitate is centrifuged, washed, and finally dried in an oven; thus, a cerium-based precursor is obtained;
[0070] Step 4: Weigh 1.0362 g (0.004775 mol) of cerium-based precursor, 0.17799 g (0.00239 mol) of potassium chloride, 0.2793 g (0.00478 mol) of sodium chloride, and then weigh 0.1307 g (0.00225 mol) of potassium fluoride, grind them separately, and then evenly disperse them in anhydrous ethanol, stir them magnetically for 30 min, and then dry them in a constant temperature drying oven at 80 ° C for 5 h to obtain a mixed salt;
[0071] Step 5: Put the mixed salt obtained in step 4 into a crucible, place it in a muffle furnace, heat it from room temperature to 850°C at 5°C / min, keep it warm for 5h, calcine it, then cool it to 400°C at 2°C / min, and finally cool it naturally to room temperature, and dry it in a constant temperature drying oven at 80°C for 5h to obtain CeO 1.91 F 0.09 Abrasive particles.
[0072] The obtained CeO 1.91 F 0.09 The abrasive particles were dispersed in deionized water and ball-milled for 10 hours. The pH value of the dispersion prepared in step 1 was adjusted to 6 with dilute nitric acid and ammonia water, and the solid content was adjusted to 0.5wt% to obtain a polishing liquid with a solid content of 0.5wt%, which was applied to a SiO2 substrate for chemical mechanical polishing. The polishing machine model was UNIPOL-1200S automatic pressure grinding and polishing machine, the lower polishing disc speed was 80r / min, the polishing head speed was 80r / min, the downward pressure was 3.5kg, the polishing time was 180s, the material removal rate was calculated by weighing the average change in glass mass before and after polishing, and an atomic force microscope (AFM) was used to observe the change in surface roughness of the polished workpiece before and after polishing.
[0073] After the prepared polishing liquid is dispersed, a portion is measured and placed in a 10 ml sub-bottle for a 5-day sedimentation test to test the suspension stability of the polishing liquid. The supernatant after sedimentation for several days is then used for other tests such as absorbance and Zeta potential to characterize the suspension stability of the polishing liquid.
[0074] Comparative Example 1
[0075] Step 1: According to the molar ratio of cerium source to precipitant of 1:0.5, 2.1711 g (0.005 mol) of cerium nitrate hexahydrate and 0.265 g (0.0025 mol) of sodium carbonate were weighed, and dissolved in deionized water to prepare a cerium source solution and a precipitant solution with a concentration of 0.5 mol / L;
[0076] Step 2: Stir the cerium source solution obtained in step 1 in a water bath at 60° C., and add the precipitant solution dropwise to form a reaction solution;
[0077] Step 3, the reaction solution in step 2 is stirred for 1 hour, and then aged in a water bath at 60°C; after the aging reaction is completed for 4 hours, the precipitate is centrifuged, washed, and finally dried in an oven; thus, a cerium-based precursor is obtained;
[0078] Step 4: Weigh 1.0850 g (0.005 mol) of cerium-based precursor, 1.8638 g (0.0250 mol) of potassium chloride, and 1.4625 g (0.0250 mol) of sodium chloride, grind them separately, and then evenly disperse them in anhydrous ethanol, stir them magnetically for 30 min, and then dry them in a constant temperature drying oven at 80° C. for 5 h to obtain a mixed salt;
[0079] Step 5. Put the mixed salt obtained in step 4 into a crucible, place it in a muffle furnace, heat it from room temperature to 800°C at 5°C / min, keep it warm for 4 hours, calcine it, then cool it to 400°C at 2°C / min, finally cool it naturally to room temperature, wash it with deionized water 5 times, disperse it in deionized water to obtain CeO2 dispersion, and finally dry it in a constant temperature drying oven at 80°C for 5 hours to obtain CeO2 abrasives.
[0080] The obtained CeO2 abrasive was ball-milled to prepare a polishing liquid with a solid content of 0.5wt%, and its pH was adjusted to 6 with dilute nitric acid and ammonia water, and applied to SiO2 substrate for chemical mechanical polishing. The polishing machine model was UNIPOL-1200S automatic pressure grinding and polishing machine, the lower polishing disk speed was 80r / min, the polishing head speed was 80r / min, the downward pressure was 3.5kg, the polishing time was 180s, and the material removal rate was calculated by weighing the mean change in glass mass before and after polishing. The atomic force microscope (AFM) was used to observe the change in surface roughness of the polished workpiece before and after polishing.
[0081] After the prepared polishing liquid is dispersed, a portion is measured and placed in a 10 ml sub-bottle for a 5-day sedimentation test to test the suspension stability of the polishing liquid. The supernatant after sedimentation for several days is then used for other tests such as absorbance and Zeta potential to characterize the suspension stability of the polishing liquid.
[0082] Figure 1 The XRD patterns of the fluorine-doped CeO2 abrasives of Examples 1-5 and the CeO2 abrasives of Comparative Example 1 are shown in FIG. Figure 1 As shown, there is no second phase peak and the crystallinity is high. Compared with the PDF card (#PDF 34-0394), it shows that the cubic fluorite structured fluorine-doped cerium oxide abrasive is successfully prepared. Then, the local magnified image is further analyzed. With the increase of the doping amount, the diffraction peak shifts to a low angle, proving that the fluorine ions are successfully doped.
[0083] Figure 2The SEM images of the fluorine-doped CeO2 abrasives of Examples 1-5 and the CeO2 abrasives of Comparative Example 1 are shown in Figure 2. When the cerium oxide abrasives synthesized by the present invention are used in chemical mechanical polishing, if the abrasive grain size is too small, the specific surface area of the abrasive grains will be large, and agglomeration will be easily formed, resulting in a low material removal rate. If the nanoparticle size is too large, scratches will be formed on the surface of the polished material, and the surface roughness will increase. Therefore, the appropriate abrasive grain size is the key to improving the chemical mechanical polishing performance. Figure 2 As shown, the size of the abrasive particles synthesized by the present invention is about 75-100 nm, with a moderate size, a narrow particle size distribution and good dispersibility.
[0084] Figure 3 The particle size distribution diagram of the fluorine-doped CeO2 abrasive particles of Examples 1-5 and the CeO2 abrasive particles of Comparative Example 1 is shown; it can be seen that the particle size distribution of the synthesized fluorine-doped cerium oxide abrasive particles is uniform and the size is moderate;
[0085] Figure 4 The figure is a comparison of the chemical mechanical polishing material removal rate and surface roughness of the CeO2 polishing liquid of Examples 1-5 and Comparative Example 1 on the SiO2 substrate; it can be seen that the polishing liquid prepared by the synthetic fluorine-doped cerium oxide abrasive has a high material removal rate. This is because the synthetic cerium oxide abrasive has a uniform particle size distribution and a moderate size. Secondly, the doping changes the chemical effect of cerium oxide (oxygen vacancy concentration and CeO2 3+ concentration).
[0086] Figure 5 is an atomic force microscope image of the surface of the SiO2 glass of Example 3; Figure 5 As shown in the figure, the surface roughness of the material is low, which is due to the fact that the morphology of the abrasive particles is mainly spherical and the size distribution of the abrasive particles is narrow.
[0087] Figure 6 Schematic diagram of the sedimentation of fluorine-doped CeO2 polishing liquid in Examples 1-5 and Comparative Example 1 CeO2; Figure 6 As shown, the suspension stability of the polishing liquid is improved compared with the polishing liquid not doped with fluorine ions, which is because fluorine doping improves the dispersibility of cerium oxide abrasive particles.
[0088] The above specific embodiments are only selected examples to clearly illustrate the effects that can be achieved by the present invention, and cannot be simply considered as all implementation schemes of the present invention. For practitioners in the relevant field, other changes can be made on the basis of the above scheme description, which cannot be exhaustively listed here. Any changes in numerical values derived from the design principles of the present invention still fall within the scope of protection of the claims of the present invention.
Claims
1. A fluorine-doped CeO 2 A method for preparing abrasive particles, It is characterized in that The following steps are involved: Step 1: weigh the raw materials according to the molar ratio of cerium source to soluble carbonate precipitant of 1:(0.5-5), and dissolve them in water respectively to prepare cerium source solution and precipitant solution with molar concentration of 0.1-0.5 mol / L respectively; Step 2: Place the cerium source solution obtained in step 1 in a water bath at 25°C to 80°C, and add the precipitant solution dropwise while stirring to form a reaction solution; Step 3, stirring the reaction solution in step 2 until it is evenly mixed, and then performing an aging reaction in a water bath at 25° C. to 90° C. for 1 h to 48 h; after the aging reaction, centrifuging and washing the precipitate, and finally drying the precipitate in an oven to obtain a cerium-based precursor; Step 4: Take the cerium-based precursor, molten salt and fluorinating agent in step 3 in a molar ratio of 1: (3-12): (0.01-0.09), grind the three raw materials separately, disperse them in anhydrous ethanol, stir them magnetically until they are evenly mixed, and then dry them to obtain a mixed salt; Step 5: Place the mixed salt obtained in step 4 in a muffle furnace at 700°C to 900°C for calcination for 2h to 6h, and finally allow it to cool naturally to room temperature. Wash and dry the product after the reaction to obtain fluorine-doped CeO 2 Abrasive particles.
2. The fluorine-doped CeO according to claim 1 2 A method for preparing abrasive particles, It is characterized in that The cerium source includes any one of hexahydrated cerium nitrate, hexahydrated cerium chloride and cerium carbonate.
3. The fluorine-doped CeO according to claim 1 2 A method for preparing abrasive particles, It is characterized in that The soluble carbonate precipitant includes any one of anhydrous sodium carbonate, ammonium carbonate and ammonium bicarbonate.
4. The fluorine-doped CeO according to claim 1 2 A method for preparing abrasive particles, It is characterized in that The stirring time described in step 3 is 0.5h to 2h.
5. The fluorine-doped CeO according to claim 1 2 A method for preparing abrasive particles, It is characterized in that The molten salt described in step 4 includes a mixture of any two or more of potassium chloride, potassium nitrate, sodium chloride, sodium nitrate and lithium chloride.
6. The fluorine-doped CeO according to claim 1 2 A method for preparing abrasive particles, It is characterized in that The fluorinating agent described in step 4 includes any one of potassium fluoride, sodium fluoride and ammonium fluoride.
7. The fluorine-doped CeO according to claim 1 2 A method for preparing abrasive particles, It is characterized in that The magnetic stirring time described in step 4 is 20 min to 40 min.
8. A fluorine-doped CeO prepared by the method according to any one of claims 1 to 7 2 Abrasive particles, It is characterized in that The stoichiometric formula is CeO 2-x F x , (0.01≤x≤0.09); size is 75~100nm.
9. A fluorine-doped CeO as claimed in claim 8 2 Application of abrasives in chemical mechanical polishing.
10. The fluorine-doped CeO according to claim 9 2 Application of abrasives in chemical mechanical polishing, It is characterized in that The following steps are used to configure fluorine-doped CeO 2 Abrasive polishing fluid: Step 1: Fluorine-doped CeO 2 The abrasive particles are dispersed in deionized water and ball-milled for 6 to 10 hours; Step 2: Use dilute nitric acid and ammonia water to adjust the pH value of the dispersion prepared in step 1 to 6, and adjust the solid content to 0.5wt% to obtain a fluorine-doped CeO with high activity and high suspension stability for chemical mechanical polishing. 2 Abrasive polishing fluid.
Citation Information
Patent Citations
Fluorine ion modified nano cerium oxide ultraviolet absorption material and uses thereof
CN101264377A
Fluorine doping method of cerium-based rare earth polishing powder
CN104419378A
Preparation method and application of CeO2 grinding particles for chemical mechanical polishing
CN114032034A
Polishing solution as well as preparation method and application thereof
CN115785818A
Spherical-like CeO2 abrasive particle as well as preparation method and application thereof
CN118421263A
